Spanish Version of Teenagers' Quality of Life (T-QoL) for Adolescents with Skin Diseases: Translation, Cultural Adaptation and Validation - L. Alonso-Naranjo; E. Berna-Rico; C. Blanco Abbad-Jaime de Aragón; R. Castañeda-Vozmediano; L. Prieto-López; A.I. Sánchez-Moya; C. Pérez-Hortet; Á. González-Cantero (Elsevier, 2023)
Background: Teenagers' Quality of Life (T-QoL) is an age-specific measure to assess QoL of teenagers suffering from different skin diseases. A validated Spanish language version is lacking. We present the translation, cultural adaptation and validation of the T-QoL into Spanish. Methods: A prospective study with 133 patients (between 12 and 19 years old), attended at the dermatology department of Toledo University Hospital, Spain (September 2019-May 2020), was carried out for the validation study. The International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guidelines were used for the translation and cultural adaptation. We evaluated the convergent validity with the Dermatology Life Quality Index (DLQI), the Children's Dermatology Life Quality Index (CDLQI) and with a Global Question (GQ) on self-assessed disease severity. We also analysed internal consistency and reliability of the T-QoL tool and confirmed its structure with a factor analysis. Results: Global T-QoL scores significantly correlated with the DLQI and the CDLQI (r = 0.75) and with the GQ (r = 0.63). The confirmatory factor analysis showed optimal fit for the bi-factor model and an adequate fit for the correlated three-factor model. Reliability indicators were high (Cronbach's α = 0.89; Guttman's Lambda 6 index = 0.91; Omega ω = 0.91) and test-retest showed a high stability (ICC = 0.85). The results were consistent with those found by the authors of the original test. Conclusion: Our Spanish version of the T-QoL tool is valid and reliable to assess QoL of Spanish-speaking adolescents with skin diseases. Resumen: Antecedentes: Teenagers' Quality of Life (T-QoL) es un cuestionario de calidad de vida específico para adolescentes con enfermedades cutáneas. Hasta el momento, no existe ningún método validado para este fin en español, por lo que presentamos la traducción, adaptación cultural y validación del T-QoL al español. Método: Se diseñó un estudio prospectivo con 133 pacientes (entre 12-19 años), atendidos en el Servicio de Dermatología del Hospital Universitario de Toledo, España (septiembre 2019-mayo 2020). Para la traducción y adaptación cultural se utilizaron las guías de la Sociedad Internacional de Farmacoeconomía e Investigación de Resultados (ISPOR). Se evaluó la validez convergente con el Índice de Calidad de Vida en Dermatología (DLQI), el Índice de Calidad de Vida en Dermatología Infantil (CDLQI) y con una Pregunta Global (GQ) sobre la gravedad de la enfermedad autoevaluada. También se analizó la consistencia interna y la fiabilidad de la herramienta T-QoL, y se confirmó su estructura con un análisis factorial. Resultados: Las puntuaciones globales de T-QoL se correlacionaron significativamente con el DLQI y el CDLQI (r = 0,75) y con la GQ (r = 0,63). El análisis factorial mostró un ajuste óptimo para el modelo bifactorial y un ajuste adecuado para el modelo de 3 factores correlacionado. Los indicadores de fiabilidad fueron altos (α de Cronbach = 0,89; índice Lambda 6 de Guttman = 0,91; Omega ω = 0,91) y el test-retest mostró una alta estabilidad (ICC = 0,85). Los resultados fueron consistentes con los encontrados por los autores de la prueba original. Conclusiones: La versión española del T-QoL es un cuestionario válido y fiable para evaluar la calidad de vida de adolescentes hispanohablantes con enfermedades cutáneas.